KEWENANGAN PEMERINTAH DAERAH KOTA KUPANG MENGGUNAKAN HAK PAKAI DAN HAK PENGELOLAAN ATAS TANAH YANG BERASAL DARI HAK MENGUASAI NEGARA - Sodak, Eksam; Pekuwali, Umbu Lily; Yohanes, Saryono (Petitum Law Journal, 2023)
The research findings indicate that the City of Kupang Regional Government has not optimally exercised its authority as the holder of the Right of Use and Management Rights over land acquired from state control. The Right of Use, covering an area of 14,041,022 square meters, controlled by the city government, is only utilized on 634,442 square meters (4.52%) for various purposes related to the City of Kupang government's tasks. Similarly, the Management Rights, covering an area of 4,809,012 square meters, are only utilized on 326,522 square meters (6.79%), either for the government's own use in facilitating governance tasks, development, and community services or in collaboration with third parties. Based on the research findings, it is recommended that the City of Kupang Regional Government, in collaboration with the National Land Agency (BPN) of Kupang, promptly plans the allocation and utilization of the Right of Use over an area of 13,406,580 square meters (95.48%) and the Management Rights over an area of 4,482,490 square meters (93.21%) to benefit the City of Kupang government, the community, and the business sector.